The Values of Islamic Education in the Story of Musa and Khadir - Andika Septio Harahap; Fajariah Panggabean; Dinda Amalia (Sufiya Journal of Islamic Studies, 2023)
The results of this study explain some of the ethics of students towards teachers in accordance with Islamic education in the story of Prophet Musa as. and Prophet Khidir as. in the perspective of Al-Munir's interpretation. This research is a type of qualitative descriptive research. Data collection is by using literature study techniques, namely data collected through several stages of review originating from books, notes, literature and various information relating to the problem to be solved from various sources both from journals and books. The results of this study show that ethics and manners are in accordance with Islamic education from the story of Prophet Musa and Prophet Khidir which consists of: (1) the value of patience, students are required to be patient when studying knowledge, (2) the value of being humble and gentle, indicating that the obligation a student of knowledge is to continue to respect and follow everything the teacher says, (3) the value of good prejudice, students should always be prejudiced against what their teacher does, (4) the value of enthusiasm in studying, with a sense of enthusiasm makes a student more easy to grasp the learning material conveyed by the teacher, (5) ethical values between teachers and students, teacher ethics to students, namely teaching knowledge according to the abilities / abilities of their students. The ethics of students towards their teachers is that students are not allowed to ask questions before being invited by the teacher and comply with the rules given by the teacher.